Compositional- and time-dependent dissipation, recovery and fracture toughness in hydrophobically reinforced hybrid hydrogels. (2nd December 2015) - Zhang, Huan; Peng, Huiying; Li, Yanqun; Xu, Yuanze; Weng, Wengui
Abstract: The compositional- and time-dependent mechanical properties, recovery, and fracture toughness of hybrid gels having chemical and transient cross-links are systematically studied. The hybrid gels are prepared via micellar copolymerization of acrylamide (AAm) with n -Butyl acrylate (nBA) and the hydrophobic associations of nBA form the transient cross-links. The hybrid gels exhibited excellent mechanical properties (ultimate strength ∼ 400 kPa), fast recovery, and high tolerance to cracks (fracture toughness up to 378.0 J m − 2 ). Swelling, tensile, and pure shear measurements all revealed that the reinforcement is more pronounced when the mole fraction of nBA is above 0.05 and/or the stretch rate is above 0.1 s −1 . The compositional dependence is related to the onset of the formation of transient network while the time-dependent mechanical responses are ascribed to the dynamics of the hydrophobic associations. We also confirmed the separability of strain and time in hydrophobically reinforced hybrid gels for the first time. Our results emphasize the role of the transient network and its responses under external loading in the design of next-generation tough gels. Graphical abstract: